PENGARUH KONSUMSI BUAH SEMANGKA MERAH (Citrullus Vulgaris Schard) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI RAWAT JALAN DI WILAYAH PUSKESMAS PERUMNAS I PONTIANAK BARAT - Hutasoit, Hermina Roselita; Waliyo, Edy (Poltekkes Kemenkes Pontianak, 2018)
Hypertension is a disorder of the blood vessels that result in oxygen supply and nutrients carried by the blood obstructed to the body tissues that need it (Vitahealth, 2006). Consumption of a diet high in fruits and vegetables, reduced sodium intake and increased potassium intake in foods can reduce the incidence of hypertension (Houston, Harper & PharmD, 2008). This study aims to determine the effect of red watermelon consumption on the decrease in blood pressure in hypertensive patients outpatient in Puskesmas Perumnas I West Pontianak. This type of research is experimental with quasi experiment design with pretest-posttest control group design. The test used is chi square test, paired t-test, wilcoxon, oneway anova and kruskal-wallis. The number of samples studied was 42 samples and the time of the research was conducted on June 2018. The results of the red watermelon in patients with hypertension with a dose of 200 gr, 250 gr and 300 gr for 4 days can lower blood pressure. The average of derivation in systolic blood pressure in the 200 gr group was -10,71 mmHg and diastolic -8,21 mmHg, average of derivation systolic blood pressure in the 250 gr group of -12,86 mmHg and diastolic -9,99 mmHg while the systolic blood pressure average of derivation in group 300 gr for -15,71 mmHg and diastolic equal to -13,57 mmHg. Suggestions in this study respondents can consume watermelon fruit as an alternative to lower blood pressure as much as 300 grams and for subsequent researchers need an additional length of time intervention to see the effect of decreased blood pressure is systolic blood pressure and diastolic responders to normal.